Tom Clancy shadow state [large type] - Woodward, M. P.; Clancy, Tom, 1947-2013 (Clancy, Tom, 1947-2013. Jack Ryan Jr. novel, 2024)
"Jack Ryan, Jr. finds himself cut off from his comrades at The Campus just when he needs them most. He's smack dab in the middle of an international conspiracy, and this may be too much for even him to handle"--